Elevation of white blood cells and platelet counts in patients having chronic periodontitis - Al-Rasheed, Abdulaziz (Elsevier, 2011)
BACKGROUND AND AIM: Many risk factors that might contribute to the pathogenesis of atherosclerosis have been proposed, including chronic inflammation and infection. Furthermore, systemic inflammatory responses to periodontal bacteria have been suggested as a pathogenetic link between periodontal disease and atherosclerosis. The purpose of this study was to estimate the white blood cell (WBC) and platelet counts in chronic periodontitis patients. MATERIALS AND METHODS: Fifty patients with chronic periodontitis and 50 patients with healthy periodontium were included in this study. Oral hygiene status, pocket probing depth (PPD) and clinical attachment level (CAL) were measured. During clinical evaluation, venous blood samples were taken to analyze the WBC and platelet counts. Statistical analysis was utilized to compare differences across groups. RESULTS: Periodontitis patients demonstrated a significantly higher WBC count (7.22 ± 1.42 × 10(9) cells/L) than that of control patients (5.64 ± 1.56 × 10(9) cells/L; P < 0.001). The platelet count of patients with chronic periodontitis (290.73 ± 56.56 × 10(9) cells/L) was also significantly higher compared to the healthy group (223.37 ± 50.27 × 10(9) cells/L; P < 0.001). CONCLUSION: Levels of WBCs and platelets are elevated in periodontitis patients compared to healthy controls.